Hate Speech Linguistic Perspectives - Guillén-Nieto, Victoria (Foundations in Language and Law [FLL], 2023)
Hate speech creates environments that are conducive to hate crimes and broad-scale conflict. This book discusses the mechanics of hate speech and its expression from a linguistic perspective. The author addresses the challenges that legal practitioners and linguists meet when dealing with hate speech, especially with the advent of social media, and offers the reader a comprehensive linguistic approach to the legal problem of hate speech.